2020
DOI: 10.1142/s2424835520500447
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Distal Radius Fractures Accompanied by Volar Lunate Facet Fragments: A Comparison between Dorsal and Volar Displaced Fractures

Abstract: Background: The treatment strategy for distal radius fractures accompanied by volar lunate facet fragment is controversial. In most cases, only the bone fragment size was discussed and a plate for distal placement is selected due to the accompanying volar lunate facet fragment regardless of the direction of bone fragment displacement. In this study, we divided distal radius fractures accompanied by volar lunate facet fragment into dorsal and volar displaced fractures, and treated these surgically based on diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 3 14 15 We used Obata et al's VLF definition, which was a length of 10 mm or less. 10 To avoid postoperative VLF displacement, the position of volar locking plates should be as distal and ulnar as possible for VLF coverage. Izawa et al showed that the plate should cover more than 65% of the VLF volar cortex to prevent postoperative fixation failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 14 15 We used Obata et al's VLF definition, which was a length of 10 mm or less. 10 To avoid postoperative VLF displacement, the position of volar locking plates should be as distal and ulnar as possible for VLF coverage. Izawa et al showed that the plate should cover more than 65% of the VLF volar cortex to prevent postoperative fixation failure.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study defined VLF as a VLF fragment that has a volar cortex length of less than 10 mm from the distal edge on a sagittal CT slice, which is cut 5 mm radial from the ulnar edge of the distal radius. 10 Evaluation of the anteroposterior (AP) radiograph is shown in ►Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects were 122 patients with dorsal-displaced DRFs treated by reduction and fixation using PVLP (42 males and 80 females, mean age: 59.2 years old) between January 2012 and December 2018. In the distal fragments of the distal radius fractures, the free bone fragments in the volar lunate facet fragment in which the longitudinal diameter of the volar bone cortex is 10 mm or less are defined as the volar lunate facet fragment [16]. The patients were divided into 13 patients with VLFF (VLFF (+) group: 9 males and 4 females, mean age: 60.0 years old) and 109 patients without VLFF (VLFF (À) group: 33 males and 76 females, mean age: 59.2 years old), and the clinical outcomes at 12 months after surgery were compared.…”
Section: Patientsmentioning
confidence: 99%